Human Fetal Scalp Dermal Papilla Enriched Genes and the Role of R-Spondin-1 in the Restoration of Hair Neogenesis in Adult Mouse Cells - Weber, Erin L.; Lai, Yung-Chih; Lei, Mingxing; Jiang, Ting-Xin; Chuong, Cheng-Ming (Frontiers in Cell and Developmental Biology, 2020)
Much remains unknown about the regulatory networks which govern the dermal papilla’s (DP) ability to induce hair follicle neogenesis, a capacity which decreases greatly with age. To further define the core genes which characterize the DP cell and to identify pathways prominent in DP cells with greater hair inductive capacity, comparative transcriptome analyses of human fetal and adult dermal follicular cells were performed. 121 genes were significantly upregulated in fetal DP cells in comparison to both fetal dermal sheath cup (DSC) cells and interfollicular dermal (IFD) populations. Comparison of the set of enriched human fetal DP genes with human adult DP, newborn mouse DP, and embryonic mouse dermal condensation (DC) cells revealed differences in the expression of Wnt/β-catenin, Shh, FGF, BMP, and Notch signaling pathways. We chose R-spondin-1, a Wnt agonist, for functional verification and show that exogenous administration restores hair follicle neogenesis from adult mouse cells in skin reconstitution assays. To explore upstream regulators of fetal DP gene expression, we identified twenty-nine transcription factors which are upregulated in human fetal DP cells compared to adult DP cells. Of these, seven transcription factor binding motifs were significantly enriched in the candidate promoter regions of genes differentially expressed between fetal and adult DP cells, suggesting a potential role in the regulatory network which confers the fetal DP phenotype and a possible relationship to the induction of follicle neogenesis.